NUMERICAL ANALYSIS OF STEEL MEMBER REMAINING COMPRESSIVE CAPACITY DURING SHIELDED METAL ARC WELDING - Mushthofa, Malik; Hardawati, Astriana (JURNAL TEKNIK SIPIL, 2024)
This study investigates the influence of Shielded Metal Arc Welding (SMAW) welding parameters on the remaining compressive capacity of angle-shaped steel members used for structural strengthening. The analysis focuses on members with thin hot-rolled profiles (40.4 x 40.4 x 4.0 mm, 50.5 x 50.5 x 5.0 mm, and 60.6 x 60.6 x 6.0 mm). A finite element model simulates the heat distribution caused by welding, leading to a temperature increase within the member. Welding scenarios are simulated using various combinations of current strength and welding speed based on the specifications for electrode type E6013. The remaining compressive capacity is determined by segmenting the cross-section based on temperature intervals and considering the member's slenderness. The analysis reveals a clear correlation between welding parameters and compressive capacity loss. Employing a higher current and lower welding speed leads to a more significant reduction in capacity due to the resulting extensive heat-affected zone (HAZ). Conversely, the lowest current and highest speed scenario minimizes the HAZ, resulting in the highest remaining compressive capacity. The analysis demonstrates that the 40.4 x 40.4 x 4.0 mm member can retain up to 51.15% of its original capacity under these optimal conditions, while the 50.5 x 50.5 x 5.0 mm and 60.6 x 60.6 x 6.0 mm members can retain 57.79% and 75.78%, respectively. In contrast, the worst-case scenario employing high current and low speed significantly reduces the remaining capacity, with reductions down to 6.79%, 10.87%, and 10.54% for the respective member sizes. These findings highlight the importance of optimizing welding parameters to minimize the negative impact on the compressive capacity of steel members during strengthening operations.